Fiscal policy over the business cycle in Germany - a tale in three acts. Evidence from a time-varying VAR analysis 1970-2008 - Christoph Priesmeier (Verein für Socialpolitik, 2010)
Large parts of the empirical economic literature state that policy makers have ex-post proven to be unable to time fiscal policy measures countercyclically. In this paper we expand the usually applied empirical approaches and allow for changing reaction patterns over time by employing not only VAR- but as well time-varying parameter VAR estimation techniques on quarterly fiscal data for Germany from 1970-2008. Our analysis shows not a general a-cyclical pattern but three distinct phases of different fiscal policy timing indicating possible misspecifications of time-invariant analyses.
Keywords: E62; E32; D78; 330